Efficient cyanation of aryl halide with K4[Fe(CN)6]⋅3H2O catalyzed by a P–O bidentate chelate palladium complex under air. (7th July 2014) - Fu, Leiqing; Li, Xiaogang; Zhu, Qiming; Chen, Sanbao; Kang, Yanping; Guo, Mengping
<x xml:space="preserve">Abstract</x> Cyanation of aryl halide with K4[Fe(CN)6]⋅3H2O has been carried out in the presence of a high‐activity catalyst: an air‐stable P–O bidentate chelate palladium complex. This method is applicable to both activated and deactivated aryl halides, and even a variety of aromatic nitriles are obtained in good yields under aerobic conditions. Copyright © 2014 John Wiley & Sons, Ltd.